Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To find the derivative of the function [tex]\( f(x) = \frac{1}{\sqrt{x}} \)[/tex] with respect to [tex]\( x \)[/tex] from first principles, we need to use the definition of the derivative. The definition states:
[tex]\[ f'(x) = \lim_{h \to 0} \frac{f(x+h) - f(x)}{h} \][/tex]
Let’s apply this definition step-by-step.
1. Step 1: Define [tex]\( f(x) \)[/tex] and [tex]\( f(x + h) \)[/tex]:
[tex]\[ f(x) = \frac{1}{\sqrt{x}} \][/tex]
[tex]\[ f(x + h) = \frac{1}{\sqrt{x + h}} \][/tex]
2. Step 2: Form the difference quotient:
[tex]\[ \frac{f(x + h) - f(x)}{h} = \frac{\frac{1}{\sqrt{x + h}} - \frac{1}{\sqrt{x}}}{h} \][/tex]
To simplify this expression, we need to find a common denominator for the fractions in the numerator:
[tex]\[ \frac{1}{\sqrt{x + h}} \text{ and } \frac{1}{\sqrt{x}} \][/tex]
The common denominator is [tex]\( \sqrt{x + h} \cdot \sqrt{x} \)[/tex]. Thus, the difference quotient becomes:
[tex]\[ \frac{f(x + h) - f(x)}{h} = \frac{\frac{\sqrt{x} - \sqrt{x + h}}{\sqrt{x(x + h)}}}{h} \][/tex]
3. Step 3: Simplify the numerator:
[tex]\[ \frac{\sqrt{x} - \sqrt{x + h}}{\sqrt{x(x + h)}} = \frac{(\sqrt{x} - \sqrt{x + h})(\sqrt{x} + \sqrt{x + h})}{\sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} \][/tex]
The numerator simplifies using the difference of squares formula:
[tex]\[ = \frac{x - (x + h)}{\sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} = \frac{x - x - h}{\sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} = \frac{-h}{\sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} \][/tex]
4. Step 4: Include [tex]\( h \)[/tex] divisor:
[tex]\[ \frac{f(x + h) - f(x)}{h} = \frac{-h}{h \sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} = \frac{-1}{\sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} \][/tex]
5. Step 5: Take the limit as [tex]\( h \)[/tex] approaches 0:
As [tex]\( h \)[/tex] approaches 0, [tex]\( x + h \)[/tex] approaches [tex]\( x \)[/tex], and [tex]\( \sqrt{x + h} \)[/tex] approaches [tex]\( \sqrt{x} \)[/tex]:
[tex]\[ \lim_{h \to 0} \frac{-1}{\sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} = \frac{-1}{\sqrt{x \cdot x}(\sqrt{x} + \sqrt{x})} = \frac{-1}{x (\sqrt{x} + \sqrt{x})} = \frac{-1}{x \cdot 2\sqrt{x}} = \frac{-1}{2x^{3/2}} \][/tex]
Therefore, the derivative of the function [tex]\( f(x) = \frac{1}{\sqrt{x}} \)[/tex] with respect to [tex]\( x \)[/tex] is:
[tex]\[ f'(x) = -\frac{1}{2x^{3/2}} \][/tex]
[tex]\[ f'(x) = \lim_{h \to 0} \frac{f(x+h) - f(x)}{h} \][/tex]
Let’s apply this definition step-by-step.
1. Step 1: Define [tex]\( f(x) \)[/tex] and [tex]\( f(x + h) \)[/tex]:
[tex]\[ f(x) = \frac{1}{\sqrt{x}} \][/tex]
[tex]\[ f(x + h) = \frac{1}{\sqrt{x + h}} \][/tex]
2. Step 2: Form the difference quotient:
[tex]\[ \frac{f(x + h) - f(x)}{h} = \frac{\frac{1}{\sqrt{x + h}} - \frac{1}{\sqrt{x}}}{h} \][/tex]
To simplify this expression, we need to find a common denominator for the fractions in the numerator:
[tex]\[ \frac{1}{\sqrt{x + h}} \text{ and } \frac{1}{\sqrt{x}} \][/tex]
The common denominator is [tex]\( \sqrt{x + h} \cdot \sqrt{x} \)[/tex]. Thus, the difference quotient becomes:
[tex]\[ \frac{f(x + h) - f(x)}{h} = \frac{\frac{\sqrt{x} - \sqrt{x + h}}{\sqrt{x(x + h)}}}{h} \][/tex]
3. Step 3: Simplify the numerator:
[tex]\[ \frac{\sqrt{x} - \sqrt{x + h}}{\sqrt{x(x + h)}} = \frac{(\sqrt{x} - \sqrt{x + h})(\sqrt{x} + \sqrt{x + h})}{\sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} \][/tex]
The numerator simplifies using the difference of squares formula:
[tex]\[ = \frac{x - (x + h)}{\sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} = \frac{x - x - h}{\sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} = \frac{-h}{\sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} \][/tex]
4. Step 4: Include [tex]\( h \)[/tex] divisor:
[tex]\[ \frac{f(x + h) - f(x)}{h} = \frac{-h}{h \sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} = \frac{-1}{\sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} \][/tex]
5. Step 5: Take the limit as [tex]\( h \)[/tex] approaches 0:
As [tex]\( h \)[/tex] approaches 0, [tex]\( x + h \)[/tex] approaches [tex]\( x \)[/tex], and [tex]\( \sqrt{x + h} \)[/tex] approaches [tex]\( \sqrt{x} \)[/tex]:
[tex]\[ \lim_{h \to 0} \frac{-1}{\sqrt{x(x + h)}(\sqrt{x} + \sqrt{x + h})} = \frac{-1}{\sqrt{x \cdot x}(\sqrt{x} + \sqrt{x})} = \frac{-1}{x (\sqrt{x} + \sqrt{x})} = \frac{-1}{x \cdot 2\sqrt{x}} = \frac{-1}{2x^{3/2}} \][/tex]
Therefore, the derivative of the function [tex]\( f(x) = \frac{1}{\sqrt{x}} \)[/tex] with respect to [tex]\( x \)[/tex] is:
[tex]\[ f'(x) = -\frac{1}{2x^{3/2}} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.